Threaded spikes for bluff body base flow control - Khan, Sher Afghan; Alrobaian, Abdul Rahman; Asad Ullah, Mohammed; Rao, Ashwin (Akademi Baru, 2019)
Although the demand for rockets and missiles has increased exponentially the problems of the gas dynamics related to these vehicles remains to be a challenge. The main problem is high-pressure associated with the shock wave in front and low-pressure recirculation bubble attached behind the vehicle at the blunt base. This barrier of wave drag due to the shock waves and the drag due to the bubble leads to a huge amount of the fuel consumption and high fluctuations in the flow field of the enlarged duct. This paper focuses mainly on the base drag and experimentally investigated the effect of the passive control in the form of the threaded spikes for bluff bodies as the base flow controller. Two threaded spikes of length 40 mm opposite to each other and attached to a control plate of diameter 80 mm and thickness 1 mm is at pitch circle diameter of 23 mm and slot of 10 mm X 10 mm at the center, placed between the nozzle and the duct to act as the passive controller. The Mach numbers considered for the investigation in the subsonic regime were 0.6, 0.7 and in the transonic regime were 0.8, 0.9 for the enlarged duct cross-sectional area of 625 mm 2 and the exit area of the nozzle considered were 100 mm2. The lengths of the enlarged duct were 100 mm, 150 mm and 200 mm. The passive control and regulating the base pressure by threaded spikes were found very efficient without any adverse effect on the flow field of the enlarged duct.